Involvement of Abnormal Gut Microbiota Composition and Function in Doxorubicin-Induced Cardiotoxicity - Huang, Jie; Wei, Shanshan; Jiang, Chuanhao; Xiao, Zijun; Liu, Jian; Peng, Weijun; Zhang, Bikui; Li, Wenqun (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives Doxorubicin (Dox), a chemotherapeutic anthracycline agent for the treatment of a variety of malignancies, has a limitation in clinical application for dose-dependent cardiotoxicity. The purpose of this study was to explore the relationship between the composition/function of the gut microbiota and Dox-induced cardiotoxicity (DIC). Methods C57BL/6J mice were injected intraperitoneally with 15 mg/kg of Dox, with or without antibiotics (Abs) administration. The M-mode echocardiograms were performed to assess cardiac function. The histopathological analysis was conducted by H&E staining and TUNEL kit assay. The serum levels of creatine kinase (CK), CK-MB (CK-MB), lactic dehydrogenase (LDH), and cardiac troponin T (cTnT) were analyzed by an automatic biochemical analyzer. 16S rRNA gene and metagenomic sequencing of fecal samples were used to explore the gut microbiota composition and function. Key Findings Dox caused left ventricular (LV) dilation and reduced LV contractility. The levels of cardiomyocyte apoptosis and myocardial enzymes were elevated in Dox-treated mice compared with the control (Con) group. 16S rRNA gene sequencing results revealed significant differences in microbial composition between the two groups. In the Dox group, the relative abundances of Allobaculum, Muribaculum, and Lachnoclostridium were significantly decreased, whereas Faecalibaculum, Dubosiella, and Lachnospiraceae were significantly increased compared with the Con group at the genus level. Functional enrichment with Cluster of orthologous groups of proteins (COG) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed that the Dox mice displayed different clusters of cellular processes and metabolism from the Con mice. The different species and their functions between the two groups were associated with the clinical factors of cardiac enzymes. Moreover, depletion of the gut microbiota could alleviate Dox-induced myocardial injury and cardiomyocyte apoptosis. Conclusions The study here shows that composition imbalance and functional changes of the gut microbiota can be one of the etiological mechanisms underlying DIC. The gut microbiota may serve as new targets for the treatment of cardiotoxicity and cardiovascular diseases.